The impact of adopting Additive Manufacturing on responsive supply chain performance - Alogla, Ageel (2021)
Additive Manufacturing (AM), or 3D printing as it is frequently known, is an umbrella term for a collection of manufacturing technologies that enables products to be manufactured layer-by-layer from three-dimensional digital data. While the costs associated with AM represents a barrier to its wider adoption, its benefits outweigh its costs when considered in some contexts. Few studies have investigated the costs and benefits of this technology from a supply chain perspective, particularly in market environments characterized by demand uncertainty. In this type of scenario, it becomes necessary to adopt higher levels of internal competencies, find the optimal way to manage inventories and flexibly respond to sudden market requirements. This thesis therefore aims to address this gap by examining three key aspects: the learning effects offered by AM, the impact of AM on inventory-related costs and the impact of AM on the critical capability of flexibility.